“The Detonation of an Act that had been taking Shape”: Nature’s Actantial Modality, Distributive Agency and Testimonial Function in Eliana Hernández and María Isabel Rueda’s La mata (2020) - Villegas Restrepo, Juan Esteban (Universidad Pedagógica y Tecnológica de Colombia, 2022)
From hermeneutic assessment of the nonhuman turnabout, and materialist ecocriticism, this article studies La mata, a documentary poem by Eliana Hernández, and illustrated by María Isabel Rueda. In this poem, nature can be read as a nonhuman arrangement network capable to predict the paramilitary massacre of El Salado in Colombia, and also as an adjuvant in this story. This reading, in turn, confirms the said agency allows for the poetic-narrative program in question to be accomplished. Similarly, the article reflects on the ways in which Hernández uses earth’s fecundated archetype which stems from the body and blood of the victims, to make the world of the nonhuman a witness of violence, but also a place of memory for the massacred and survivors.